Comparing health promoting lifestyle in HIV positive and HIV negative individuals - Fariba Ebrahimbabaie; Mojtaba Habibi; Saeid Ghodrati (Journal of Education and Community Health)
Background and Objective: Lifestyle is one of the factors playing an important role in disease involvement and treatment. In this study, we aimed to compare health-promoting lifestyle between HIV-positive and HIVnegative individuals in Tehran, Iran. Materials and Methods: This cross-sectional study was conducted among 147 HIV-positive individuals who referred to Imam Khomeini Hospital of Tehran, Iran, and 150 HIV-negative individuals during 2014 to 2016. We used the Health Promoting Lifestyle Profile II (HPLP-II) questionnaire, which encompasses six domains of health responsibility, physical activity, nutrition, interpersonal relationships, spiritual growth, and stress management. The participants were selected using the convenience sampling method. To analyze the data, multivariate analysis of variance (MANOVA) was run in SPSS, version 22. Results: MANOVA reflected a significant difference between HIV positive and HIV-negative individuals in lifestyle (P<0.001). The two groups were different in terms of health responsibility (F[1,245]=42.44, P<0.001) and physical activity (F[1,245]=6.03, P<0.05), with HIV-positive obtaining lower scores than the HIV negative patients. However, the two groups did not differ significantly with regards to the nutrition, interpersonal relationships, spiritual growth, and stress management domains (P>0.05). Conclusion: Considering the limited data on the lifestyle of HIV positive patients in Iran, awareness regarding various lifestyle aspects of these individuals can yield valuable information to promote HIV-positive individuals’ life status and interventional programs. Future studies are recommended to focus more attention on lifestyle promotion among HIVpositive individuals.